Autobiograficzne filmy Terayamy Shujiego na tle japońskiej Nowej Fali. Na pograniczu kina i teatru - KAROLAK, NIKODEM (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Terayama Shūji’s autobiographical fi lms against the background of the Japanese New Wave. On the boundary between cinema and theatre Shuji Terayama (1935-1983) was a Japanese avant-garde poet, novelist, film and theatre director, as well as the founder of the very eccentric Japanese theatrical troupe named Tenjo Sajiki. He is a world-renowned character, regarded as one of the most original and influential figures in Japanese modern art. Although he was considered the originator of a series of scandalous events, he was still supported by a range of important Japanese and Europeans stage directors, art designers, writers and poets who who lavishly praised him for his revolutionary art techniques and his genius capable of invoking in the audience something more than just the mere interpretation of a play. The paper revolves around Terayamas representative film works in which cinema and theatre intertwine with each other. The author depicts Terayamas films within the framework of the Japanese New Wave genre, concentrating not only on their intertextual values, but also on Terayamas autobiographical events - indispensable knowledge that facilitates understanding of his works.